2023
DOI: 10.1155/2023/4295613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Intervention on Knowledge and Level of Adherence among Hemodialysis Patients: A Randomized Controlled Trial

Abstract: Purpose. The purpose of the study was to assess the impact of an educational intervention on the level of knowledge and adherence to the treatment regimen among hemodialysis (HD) patients as well as to describe the association between these variables. Methods. In this randomized controlled trial, 160 HD patients at an HD centre of a 2030-bed tertiary teaching hospital in Southern India were randomly assigned into intervention (N = 80, received education and a booklet) and control (N = 80, received standard car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The studies included in this review have demonstrated an increase in adherence to fluid restriction [ 13 , 15 , 39 , 40 , 43 , 44 , 49 ], potassium and phosphate intake [ 13 ], dietary restriction [ 15 , 39 , 40 , 44 , 49 ], specific cooking methods [ 28 ], vegetable preferences [ 28 ], sodium intake adherence [ 13 ], and reduction in the frequency of non-adherence to the diet [ 23 ], frequency of non-adherence to fluid restriction [ 23 ], the score of non-adherence to sweets high in P (phosphorus) [ 27 ], and starch high in P [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies included in this review have demonstrated an increase in adherence to fluid restriction [ 13 , 15 , 39 , 40 , 43 , 44 , 49 ], potassium and phosphate intake [ 13 ], dietary restriction [ 15 , 39 , 40 , 44 , 49 ], specific cooking methods [ 28 ], vegetable preferences [ 28 ], sodium intake adherence [ 13 ], and reduction in the frequency of non-adherence to the diet [ 23 ], frequency of non-adherence to fluid restriction [ 23 ], the score of non-adherence to sweets high in P (phosphorus) [ 27 ], and starch high in P [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies in our review were subject to certain limitations. This included insufficient results to draw any conclusions [ 12 ], challenges in generalizing the findings [ 13 , 15 , 27 , 35 , 48 , 50 , 51 ], language difficulties among patients [ 13 ], a lack of detail on the effect of the intervention elements [ 13 ], the possibility of contamination of information between patient groups [ 14 , 19 , 34 , 44 ], uncontrolled variables [ 14 , 21 , 22 , 26 , 29 , 31 , 37 ], short duration of studies, interventions, or follow-up [ 15 , 19 , 27 , 30 , 35 , 41 , 51 ], the patients already being familiar with educational content [ 17 ], small sample size [ 29 , 30 , 37 , 41 , 46 , 49 , 52 ], self-selection bias [ 52 ], not all information being analyzed [ 20 , 48 ], subjective results linked to patient declarations [ 23 ], inaccurate assessment tools [ 42 ], possible Hawthorne effect [ 30 ], interventions conducted in a single center [ 30 , 41 ], and the possibility of social desirability effect bias [ 39 ,…”
Section: Discussionmentioning
confidence: 99%